2023
DOI: 10.3390/math11041037
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Using Cloud Computing in Sustainable Construction in Nigeria: A Fuzzy Synthetic Evaluation

Abstract: This study aims to assess the barriers impeding cloud computing (CC) applicability in sustainable construction. A total of 11 barriers in the use of CC were identified for the literature review. A questionnaire survey was used to collect the data from construction stakeholders. In total, 101 valid responses were obtained and analyzed using mean ranking, normalized value (NV), overlapping analysis, Kruskal–Wallis H test, exploratory factor analysis (EFA), and fuzzy synthetic evaluation (FSE). The EFA extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Oke et al [45] investigated CC barriers using exploratory factor analysis (EFA) and partial least square (PLS)-SEM for developing a sustainable construction environment and concluded that social barriers are the most challenging ones. Omer [46] further considered a case study on sustainable construction to analyze 11 CC barriers under a fuzzy environment.…”
Section: Role Of Mcdm For Promoting Sustainability In Cloud Computingmentioning
confidence: 99%
“…Oke et al [45] investigated CC barriers using exploratory factor analysis (EFA) and partial least square (PLS)-SEM for developing a sustainable construction environment and concluded that social barriers are the most challenging ones. Omer [46] further considered a case study on sustainable construction to analyze 11 CC barriers under a fuzzy environment.…”
Section: Role Of Mcdm For Promoting Sustainability In Cloud Computingmentioning
confidence: 99%
“…The MSR, standard deviation, and normalization technique were further used to rank the drivers for DfD implementation in the GCI. The NV indicates adjusting the survey items to standardized values between zero and one (Omer et al, 2023). In this manner, the variable that has the highest mean value converts to one, while the least mean value is converted to zero.…”
Section: Survey Design Administration and Analysismentioning
confidence: 99%
“…Equation ( 1) is used to compute the NV of the various drivers. According to Omer et al (2023), an NV of 0.60 was used to detect the crucial variables. In this regard, all the variables/drivers with NV of 0.60 and above were considered crucial to implementing DfD in the GCI.…”
Section: Survey Design Administration and Analysismentioning
confidence: 99%